ChemInform Abstract: Rhodium‐ and Iridium‐Catalyzed Dehydrogenative Cyclization Through Double C—H Bond Cleavages to Produce Fluorene Derivatives. Issue 25 (3rd June 2013) - Itoh, Masaki; Hirano, Koji; Satoh, Tetsuya; Shibata, Yu; Tanaka, Ken; Miura, Masahiro
Abstract Cyclization of 2, 2‐diarylalkanoic acids proceeds through double C—H bond cleavage and decarboxylation in the presence of copper acetate and a Rh‐catalyst.